Relationship and resource management in operations. - Loader, David (Operations management series (Securities Institute))
Relationship and Resource Management in Operations' explains in practical terms the importance of the business relationships with internal and external counterparts while demonstrating how things can go wrong and what causes the situation. The authors examine the need to instil cultures in the team focusing on client service, risk and cost effectiveness. The text covers, via practical examples, the kind of scenario managers or supervisors might face in their role and shows what decisions could and should be made. The operations function in a financial organization is crucial to the success of.